2015
DOI: 10.1088/0264-9381/32/3/035026
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of higher dimensional nonrotating isolated horizons from loop quantum gravity

Abstract: In this paper, we extend the calculation of the entropy of the nonrotating isolated horizons in 4 dimensional spacetime to that in a higher dimensional spacetime. We show that the boundary degrees of freedom on an isolated horizon can be described effectively by a punctured SO(1, 1) BF theory. Then the entropy of the nonrotating isolated horizon can be calculated out by counting the microstates. It satisfies the Bekenstein-Hawking law.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 58 publications
0
20
1
Order By: Relevance
“…Their internal degrees of freedom are traced out and the number of their boundary degrees of freedom gives the entropy of the IH. In contrast, in the previous approach [20,21,24,36] since only the Palatini action is considered, the symplectic form has two terms, the bulk term and the boundary term. The resulted Hilbert space is also the tensor product of the bulk and the boundary Hilbert space.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Their internal degrees of freedom are traced out and the number of their boundary degrees of freedom gives the entropy of the IH. In contrast, in the previous approach [20,21,24,36] since only the Palatini action is considered, the symplectic form has two terms, the bulk term and the boundary term. The resulted Hilbert space is also the tensor product of the bulk and the boundary Hilbert space.…”
Section: Discussionmentioning
confidence: 95%
“…The reason is that the eigenvalue equation (4.1) for the flux operator is different from the Ref. [21] with a factor 2, so the flux operator have the same eigenvalues, thus the same physics. We choose this form since it gives the same value for both SU(2) in 4 dimension and SO(D) in arbitrary dimension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous work [24][25][26][27][28][29][30], it was shown that the boundary degrees of freedom can also be described by a BF theory. Since both the BF theory and the massless scalar field theory are on the horizon, the relation between those two theories need further investigated.…”
Section: The Other Component Transforms Intōmentioning
confidence: 99%
“…This action is closely related to loop quantum gravity [14][15][16][17]. Another advantage is that, when considering a black hole, the boundary degrees of freedom can be described by a SO(1, 1) BF theory [18][19][20][21][22]. In the following section we set 8πG = 1.…”
Section: Introductionmentioning
confidence: 99%